2020
DOI: 10.3390/s20041173
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotube Yarn Microelectrodes Promote High Temporal Measurements of Serotonin Using Fast Scan Cyclic Voltammetry

Abstract: Carbon fiber-microelectrodes (CFMEs) have been the standard for neurotransmitter detection for over forty years. However, in recent years, there have been many advances of utilizing alternative nanomaterials for neurotransmitter detection with fast scan cyclic voltammetry (FSCV). Recently, carbon nanotube (CNT) yarns have been developed as the working electrode materials for neurotransmitter sensing capabilities with fast scan cyclic voltammetry. Carbon nanotubes are ideal for neurotransmitter detection becaus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 47 publications
2
33
0
Order By: Relevance
“…However, such N-shaped FSCV waveforms cannot be effectively used to detect DA since DA sensing requires a more negative holding potential to facilitate the cationic adsorption on the electrode surface and to detect the DA reduction peak (Swamy and Venton 2007a;Zestos et al 2014). On the other hand, different high surface area carbon materials (Swamy and Venton 2007a;Yang et al 2017;Zestos et al 2014), have been investigated and shown promising fouling resistance to 5-HT reaction byproduct (Mendoza et al 2020;Swamy and Venton 2007a;Weese et al 2019;Zestos et al 2014), which has been mainly attributed to the presence of defect sites in high density (Mendoza et al 2020;Zestos et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…However, such N-shaped FSCV waveforms cannot be effectively used to detect DA since DA sensing requires a more negative holding potential to facilitate the cationic adsorption on the electrode surface and to detect the DA reduction peak (Swamy and Venton 2007a;Zestos et al 2014). On the other hand, different high surface area carbon materials (Swamy and Venton 2007a;Yang et al 2017;Zestos et al 2014), have been investigated and shown promising fouling resistance to 5-HT reaction byproduct (Mendoza et al 2020;Swamy and Venton 2007a;Weese et al 2019;Zestos et al 2014), which has been mainly attributed to the presence of defect sites in high density (Mendoza et al 2020;Zestos et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…CNTYM also has an advantage over CFM in distinguishing electroactive species, as it exhibits sharper peaks in response to DA, AA, and other neurochemicals, due to faster electron transfer kinetics. Sensors incorporating CNT yarn have been recently reported for the detection of DA, 5-HT, and glucose [ 83 , 84 , 85 ].…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“… 31 35 Fast-scan cyclic voltammetry (FSCV) coupled with CFMEs is a commonly used electrochemical technique to detect neurotransmitters in the brain with subsecond temporal resolution. 32 , 34 , 36 39 , 65 In recent years, it has been explored to study the rapid purinergic signaling in the brain. Specifically, the Venton laboratory showed that adenosine can be detected with FSCV utilizing the triangle waveforms at high (1.45 V) switching potentials.…”
Section: Introductionmentioning
confidence: 99%